Private and confidential - Graham R. Howarth (South African Family Practice)
In the medical arena the HIV pan-epidemic has brought issues surrounding the concepts of privacy and confidentiality into the spotlight. Issues of privacy and confidentiality are further exacerbated by large computer databases that store information that can then be manipulated, transmitted and accessed. It is the accessing of this data where the potential problems lie.